Implementasi Fmadm Untuk Mendukung Keputusan Pemilihan Jenis Lampu Di Laboratorium Teknologi Informasi Politeknik Negeri Padang - Nova, Fitri (Department of Informatics Engineering, 2016)
Abstrac – Lighting installation is very necessary in designing a building. The amount oflight intensity on each room is different depending on the us ability of the room it self. Simple Additive weighting (SAW) method could be used in selecting the right lamp. The greater the value of alternative earn edit the better alternative. Based on this SAW method, it is advisable touse lights that are LED with the highest on value of 9.66, then the TL lamps with a criteria on value of 6.93.